2018
DOI: 10.1111/hepr.13001
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal interactions between bile acids and gut microbiota in human liver diseases

Abstract: The gut microbiota (GM) play a central role in their host's metabolism of bile acids (BAs) by regulating deconjugation, dehydroxylation, dehydrogenation, and epimerization reactions to generate unconjugated free BAs and secondary BAs. These BAs generated by the GM are potent signaling molecules that interact with BA receptors, such as the farnesoid X receptor and Takeda G-protein-coupled receptor 5. Each BA has a differential affinity to these receptors; therefore, alterations in BA composition by GM could mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 130 publications
(226 reference statements)
0
33
0
1
Order By: Relevance
“…Increasing evidences suggested that bile acids (BAs) play a critical role in chronic liver diseases . The alteration of BAs has been shown to be closely related with various liver diseases, like nonalcoholic fatty liver disease (NAFLD), alcoholic liver disease and cirrhosis and liver cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences suggested that bile acids (BAs) play a critical role in chronic liver diseases . The alteration of BAs has been shown to be closely related with various liver diseases, like nonalcoholic fatty liver disease (NAFLD), alcoholic liver disease and cirrhosis and liver cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Ursodeoxycholic acid (UDCA) and chenodeoxycholic acid (CDCA) are widely used as pharmaceutical ingredients. [1] UDCA can be employed to treat gallstones, [2] to improve the digestion of fatty acids, to reduce cholesterol absorption and, in cases of cholestatic diseases, to stimulate the liver functions. [3] CDCA has been used for the same treatments, but its side effects made the use in clinical treatment less desiderable than UDCA.…”
mentioning
confidence: 99%
“…Bile acids are amphipathic molecules that facilitate absorption of dietary fat and lipophilic vitamins in the small intestine. Bile acids also act as signalling molecules controlling glucose, lipid and energy homoeostasis by activating farnesoid X receptor (FXR) and Takeda G‐protein receptor‐5 (TGR5) . Bile acids have differing potencies for activating FXR and TGR5.…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids are synthesised in the hepatocytes as primary bile acids (cholic acid and chenodeoxycholic acid in humans), which are transformed to secondary bile acids (deoxycholic acid and lithocholic acid) with multistep 7α‐dehydroxylation by intestinal bacteria (Figure ). The human gut microbiome may have an impact on FXR/TGR5 signalling by manipulating the availability and strength of bile acid ligands through bile acid metabolism . Recent evidence shows a role for the gut microbiome in insulin resistance, obesity and associated metabolic disturbances, raising interest in the gut microbiome's relationship with NAFLD/NASH pathogenesis .…”
Section: Introductionmentioning
confidence: 99%